2001
DOI: 10.1073/pnas.251547398
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in papillary thyroid carcinoma reveals highly consistent profiles

Abstract: Papillary thyroid carcinoma (PTC) is clinically heterogeneous. Apart from an association with ionizing radiation, the etiology and molecular biology of PTC is poorly understood. We used oligobased DNA arrays to study the expression profiles of eight matched pairs of normal thyroid and PTC tissues. Additional PTC tumors and other tissues were studied by reverse transcriptase-PCR and immunohistochemistry. The PTCs showed concordant expression of many genes and distinct clustered profiles. Genes with increased ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
299
5
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(348 citation statements)
references
References 36 publications
39
299
5
5
Order By: Relevance
“…We and others have previously shown that papillary thyroid carcinoma could be separated from benign nodules, ie follicular adenomas and hyperplastic nodules, by their mRNA expression profiles using cDNA microarray analysis. [42][43][44] By qRT-PCR evaluation, our preliminary data also showed that by using fresh-frozen materials, most cases of papillary carcinoma and follicular adenoma can also be separated by their expression of a small panel of several genes, namely CK19, CITED1, galectin 3, deiodinase 1, thyroglobulin, and pendrin. 45 However, these mRNA-based assays were found to be less reliable when applied to formalin-fixed, paraffin-embedded tissues, primarily due to the suboptimal RNA qualities in these specimens (unpublished data).…”
Section: Discussionmentioning
confidence: 66%
“…We and others have previously shown that papillary thyroid carcinoma could be separated from benign nodules, ie follicular adenomas and hyperplastic nodules, by their mRNA expression profiles using cDNA microarray analysis. [42][43][44] By qRT-PCR evaluation, our preliminary data also showed that by using fresh-frozen materials, most cases of papillary carcinoma and follicular adenoma can also be separated by their expression of a small panel of several genes, namely CK19, CITED1, galectin 3, deiodinase 1, thyroglobulin, and pendrin. 45 However, these mRNA-based assays were found to be less reliable when applied to formalin-fixed, paraffin-embedded tissues, primarily due to the suboptimal RNA qualities in these specimens (unpublished data).…”
Section: Discussionmentioning
confidence: 66%
“…To date, a number of microarray studies have shown metallothioneins to be downregulated in thyroid carcinoma. 7,14,15 Huang et al 14 expanded on their initial microarray experiment by trying to identify novel tumour suppressor genes involved in thyroid carcinogenesis. They found that MT1G was downregulated in papillary thyroid carcinoma consequent to hypermethylation.…”
Section: Expression Patternsmentioning
confidence: 99%
“…Molecular and immunohistochemical studies directed to detect specific gene profiles and related proteins in thyroid cancer have been extensively reported in literature (Bartolazzi et al, 2001;Huang et al, 2001;Ruco et al, 2001;Wreesmann et al, 2002). Experimental data, mostly arising from the molecular analysis of papillary thyroid carcinoma (PTC), contributed to identify a panel of genes overexpressed in thyroid malignancy.…”
mentioning
confidence: 99%
“…Experimental data, mostly arising from the molecular analysis of papillary thyroid carcinoma (PTC), contributed to identify a panel of genes overexpressed in thyroid malignancy. Among these genes, FN-1 (fibronectin-1), and MET (hepatocyte growth factor receptor) gene have been found consistently overexpressed in PTC (Huang et al, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation